Interest in Entrepreneurship in Vocational School 9 Bandung Students - Amemiya Maneko Putri; Tati Setiawati; Ai Nurhayati (Media Pendidikan Gizi dan Kuliner, 2023)
Based on data obtained through the Public Relations of SMKN 9 Bandung, culinary arts graduates in the last 3 years have the largest percentage, namely 68.75% employed, the lowest percentage is entrepreneurship at 0% and the highest percentage is unemployed at 37.50%. The aim of this research is to determine the interest factors of SMKN 9 Bandung students. Researchers conducted research on entrepreneurial interest among students at SMKN 9 Bandung using quantitative descriptive and data collection using questionnaires. The approach used in this research is quantitative because the data processed is in the form of numbers. Data analysis in this research refers to a Likert scale, with a population of 101 and the author uses a total sample so that the number of samples is the same as the population. The results of this research can be seen based on internal and external factors with the average being at high levels. This can motivate students to plan entrepreneurship and start entrepreneurship and internal and external factors rely on each other and go hand in hand. With this research, it is hoped that students, schools and educational institutions will be more aggressive in encouraging and motivating students to start a business, either in the form of programs or training.